Why business integrity can be a strategic response to ethical challenges - Malan, Daniel; Taylor, Alison; Tunkel, Anna; Kurtz, Birgit (MIT Sloan Management Review, 2022)
To better understand the key challenges and success factors driving some organizations' adoption of a holistic approach to ethical and responsible business, the authors interviewed leaders from more than two dozen large companies and multilateral institutions. They found that independent and autonomous leadership plays an important role, but companies must also break down internal silos to create strategic alignment and collaboration and build a culture of integrity.
Includes bibliographical references
Keywords: Business ethics; Corporations -- Moral and ethical aspects; Morale des affaires; Sociétés; Aspect moral; Corporations; Moral and ethical aspects